2013
DOI: 10.4103/0019-5154.108074
|View full text |Cite
|
Sign up to set email alerts
|

Nevus depigmentosus treated with suction blister grafting: Follow-up after 10 years

Abstract: Nevus depigmentosus is a congenital hypomelanotic condition for which no effective treatments are available. The hypopigmentation is permanent and enlarges in proportion with growth in the person. Here, I report a patient of nevus depigmentosus on whom we performed suction blister grafting and the resultant pigmentation was satisfactory even at a follow-up after 10 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Conventional surgical modalities used in the treatment of vitiligo, like punch grafting or melanocyte keratinocyte transplantation procedures, may not be effective in treating ND as the whole area needs to be covered with the epidermal sheeting . There are very few reports on the surgical management of ND, probably in part due to the benign nature . We find that we were able to achieve near normal, uniform, and acceptable pigmentation with suction blister grafting technique for ND.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…Conventional surgical modalities used in the treatment of vitiligo, like punch grafting or melanocyte keratinocyte transplantation procedures, may not be effective in treating ND as the whole area needs to be covered with the epidermal sheeting . There are very few reports on the surgical management of ND, probably in part due to the benign nature . We find that we were able to achieve near normal, uniform, and acceptable pigmentation with suction blister grafting technique for ND.…”
mentioning
confidence: 57%
“…2 There are very few reports on the surgical management of ND, probably in part due to the benign nature. [3][4][5] We find that we were able to achieve near normal, uniform, and acceptable pigmentation with suction blister grafting technique for ND. Somesh et al, have reported the use of suction blister grafting for ND and although they were able to demonstrate repigmentation, one of the complications noted was intergraft depigmentation.…”
mentioning
confidence: 99%
“…Studies of 308‐nm xenon chloride excimer laser show high recurrence rates . Suction blister grafting was effective in a few patients . Melanocyte‐keratinocyte transplantation has shown mixed results .…”
Section: Treatmentmentioning
confidence: 99%
“…47,48 Suction blister grafting was effective in a few patients. 45 Melanocyte-keratinocyte transplantation has shown mixed results. 8 Recurrence of ND is common after treatment with epidermal skin grafts.…”
Section: Indeterminate Leprosymentioning
confidence: 99%
See 1 more Smart Citation